Threat induction biases processing of emotional expressions - Flechsenhar, Aleya; Levine, Seth; Bertsch, Katja (Frontiers in psychology, 2022)
Threats can derive from our physical or social surroundings and bias the way we perceive and interpret a given situation. They can be signaled by peers through facial expressions, as expressed anger or fear can represent the source of perceived threat. The current study seeks to investigate enhanced attentional state and defensive reflexes associated with contextual threat induced through aversive sounds presented in an emotion recognition paradigm.